The Mutation in the N-Terminal Domain of RGS4 Disrupts PA-Conferred Inhibitory Effect on GAP Activity. Issue 4 (August 2003) - Ou-Yang, Ying-Shi; Tu, Yaping; Yang, Fuyu
Abstract : Regulator of G protein signaling (RGS) proteins are GTPase-activating proteins (GAP) for G protein α-subunits and are thought to be responsible for rapid deactivation of G protein mediated signaling pathway. In this present study, we demonstrate that PA is the most efficient candidate to inhibit GAP activity of RGS4. The functional significance of N -terminus of RGS4 in respose to PA-granted inhibition on GAP activity has been studied with the site mutation in the N -terminus of RGS4. These site-directed mutations in the N -terminal domain do not severely disrupt its association with liposomes of PA. However, RGS4L23E diminishes the inhibition of GAP activity by PA compared with the wild type RGS4, whereas RGSR22E abrogates the inhibitory effect by PA on GAP activity. The correspondent conformational discrepancy in the RGS domain of these mutants in the presence of PA vesicles was detected from fluorescence experiments. It is suggested that the functional pertinence between the N -terminus and RGS domain may be important to modulate PA-conferred inhibitory effect on its GAP activity.